Sistem Pendukung Keputusan Pemilihan Calon Ketua Program Studi Menerapkan Metode VIKOR - Feby Kristin Pardosi; Nelly Astuti Hasibuan (Building of Informatics, Technology and Science (BITS), 2021)
The head of the study program is one of the important people in the agency who is responsible for managing and managing each channel from high school or university. The head of study program also has tasks such as arranging plans and activities, evaluating the implementation of educational activities and so forth. Before the appointment of the head of the Study Program, there will certainly be a nomination for the head of the Study Program who has at least more than 3 lecturers and staff who have requirements. The method used in this decision support system is the VIKOR Method (Visekriterijumsko Kompromisno Rangiranje). This method performs an evaluation of alternatives and determines the ideal compromise solution, so that this system can later be useful for high schools or universities in choosing the head of study programs.